EVALUASI KEBIJAKAN ALOKASI DANA DESA DALAM PEMBANGUNAN DESA DI DESA JETISKARANGPUNG KECAMATAN KALIJAMBE KABUPATEN SRAGEN - Handayani, Novita Ayu (Master of Public Administration, Universitas Slamet Riyadi, 2019)
Village funds allocation policy, is a form of government policy in orderto support the autonomy of the village in the financial field that iscurrently implemented using Law Number 6 year 2014, which causesfunds transfer to the Government The village is increasing with the aimthat the village government can be more independent of organizing publicservices to the community and access to the welfare distribution of thevillage community for the better. The implementation of ADD policy inJetiskarangpung village of Kalijambe District has been running from2015 until now which is expected to improve the development,empowerment and economimi of society. This research aims to know andanalyze and evaluate the policy of village fund allocation in villagedevelopment in Jetiskarangpung village, Kalijambe District, Sragen hasfulfilled the effectiveness, efficiency, adequacy, alignment ,responsiveness and accuracy. This research uses qualitative descriptivemethods. Primary data sources are village heads, village devices andpublic figures, while secondary data are documents relating to theresearch variables. The data collection techniques used are interviews anddocumentation. Data analysis techniques use qualitative analysisconsisting of data reduction processes, data presentation, and datawithdrawal stages and data verification.The results showed that: (1) The Village Fund allocation policy inJetiskarangpung Sub-district of Kalijambe district of Sragen wasimplemented in accordance with the results of the Village developmentdeliberation, which is taken from the results of all public inputs, and isbased on Regulations, which need to be continued for the next yearperiod. Village Fund allocation policy in Jetiskarangpung village hasfulfilled the criteria of effectiveness, efficiency, adequacy, grading,responsiveness and accuracy. (2) Village funds allocation policy in theVillage development in Jetiskarangpung village has fulfilled itsobjectives and goals in accordance with the regulation of the RegentSragen on the implementation of Village Fund allocation directiveKey words: effectiveness, efficiency, adequacy, leveling, responsiveness,and accuracy